2017
DOI: 10.3389/fendo.2017.00318
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis of Mobile Health Applications on Diabetes Mellitus

Abstract: Diabetes self-management offers an opportunity to patients to be actively involved in managing their conditions and modifying lifestyle behaviors to attain positive health outcomes. With the unprecedented growth of mobile technology, smartphone plays a role in supporting diabetes self-management. Nonetheless, selecting appropriate mobile applications (apps) is challenging for patients. Thus, this study aimed to evaluate and compare the contents and features of mobile medical apps for diabetes self-management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(43 citation statements)
references
References 23 publications
(33 reference statements)
0
42
0
1
Order By: Relevance
“…Interoperability and standardisation Consumers use a variety of mobile technological platforms, including Android and Apple iOS. Android and Apple iOS are the dominant platforms in the US market, with a keyword search for 'diabetes' performed in the Apple and Google Play stores in 2017 identifying 246 available apps for Android and 100 for Apple iOS [70]. As of 2012, more than 75% of physicians in the USA use Apple iOS devices [71].…”
Section: Issues Faced By the Diabetes Communitymentioning
confidence: 99%
“…Interoperability and standardisation Consumers use a variety of mobile technological platforms, including Android and Apple iOS. Android and Apple iOS are the dominant platforms in the US market, with a keyword search for 'diabetes' performed in the Apple and Google Play stores in 2017 identifying 246 available apps for Android and 100 for Apple iOS [70]. As of 2012, more than 75% of physicians in the USA use Apple iOS devices [71].…”
Section: Issues Faced By the Diabetes Communitymentioning
confidence: 99%
“…Although diabetes management software has been available since the early 1980s, the rapid growth in digital communications technologies (e.g., smartphones, tablets) has prompted the development of a plethora of new selfmanagement tools for patients via mobile health (mHealth) apps. In their 2017 report, Izahar et al 13 identified 346 mHealth apps specifically for self-diabetes management that were available from the Apple iTunes and/or Google Play app stores.…”
Section: Introductionmentioning
confidence: 99%
“…Descriptive information regarding the name of developer, latest update, and operating system of the applications was collected. Based on the exhaustive literature review (Izahar et al, 2017;Demidowich, Lu Tamler, & Bloomgarden, 2012), the applications were then categorized and evaluated the availability of the following features; (1) information support; (2) subscription requirement;…”
Section: Methodsmentioning
confidence: 99%